Air Transport Association of America and Others v. Secretary of State for Energy and Climate Change. (2017) - Unknown
Abstract : Air — Legal regime of international aviation — Chicago Convention, 1944 — Environmental protection — Rights of State of landing and take-off — Whether extending to regulating aircraft of foreign registration above the high seas and in air space of other States — Whether such regulation required to be based on multinational agreement Environment — Treaties — Greenhouse gases — Emission allowances — European Union scheme for greenhouse gas emission allowance trading — Inclusion of aviation activities in that scheme through Directive 2008/101/EC — Whether certain international agreements and principles of customary international law could be relied upon to challenge validity of Directive 2008/101/EC — Whether Directive 2008/101/EC contravening Chicago Convention, 1944 — Kyoto Protocol to the United Nations Framework Convention on Climate Change, 1997 — Open Skies Agreement between European Union and United States of America, 2007 — Customary international law Relationship of international law and municipal law — Treaties — European Union — Treaty to which all European Union States party — Whether binding on European Union — Chicago Convention, 1944